Optimal Fishery with Coastal Catch - Hannes Uecker; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
In many spatial resource models it is assumed that the agent is able to determine the harvesting activity over the complete spatial domain. However, agents frequently have only access to a resource at particular locations at which the moving biomass, such as fish or game, may be caught or hunted. To analyse this problem, we set up a simple optimal control model of boundary harvesting. Using the Pontryagin's Maximum Principle we derive the associated canonical system, and numerically compute canonical steady states and optimal time dependent paths, and characterise the optimal control and the associated stock of the resource. Finally, we extend our model to a predator-prey model of the Lotka-Volterra type, and show how the presence of two species enriches the results of our basic model. For both models we illustrate the dependence of the optimal steady states and the optimal paths on the cost parameters.
Keywords: Q22; C61; 330; boundary control; bioeconomics; optimal harvesting; coastal fishing; infinite time horizon; predator-prey model; Lotka-Volterra